Discursos dos Deputados e Senadores do Congresso Nacional Brasileiro (2010-2014): tendências predominantes sobre a concepção de educação - Campos, Janaina Fatima Sabrina de (2017)
The National Education Plan - PNE (2014-2024) processed in the Brazilian National Congress during the years 2010 to 2014. In the Chamber of Deputies as Draft Law Nº 8.035/2010, in the period from 2010 to 2012, returning in 2014 to final analysis, and in the Federal Senate as Draft Law Nº 103/2012, in the period from 2012 to 2014, until it is sanctioned by President Dilma Rousseff, in Law Nº 13.005/2014. Throughout the almost five years of the Proceedings of the Law, much was discussed about Education in the Brazilian National Congress, entering as a list of the Speeches of Deputies and Senators, many in the Commissions in which the Draft Laws were appreciated, as well as in the Sessions Legislative Plenaries of the Chamber of Deputies and the Federal Senate. This research, therefore, aimed to answer the following problem: What are the predominant trends on the conception of Education underlying the speeches of Deputies and Senators of the National Congress, from 2010 to 2014? In order to respond to the problem, two specific objectives were defined: a) To understand the relationship between the State, Social / Educational Policy and the Draft Law Nº. 8.035 / 2010 and Draft Law Nº 103/2012 in the Brazilian National Congress ; b) to analyze the predominant tendencies of the conception of Education underlying the Discourses of Deputies and Senators of the National Congress, from 2010 to 2014. It is a Documentary Research in which the selection of the sources occurred through the access to the Discourses available in the site of the Chamber of Deputies, speeches and shorthand notes from 2010 to 2012 and 2014, and the Federal Senate, Federal Senate Diary, from 2012 to 2014, which correspond to the process of Draft Law. As a result of the analysis of the content of the speeches of the Deputies and Senators two objectives were obtained: Education and Economic Development and Work, Work and Poverty. With this, it can be concluded that it is a predominantly educational trend that underlies the Speeches of Deputies and Senators and liberals, having a relationship with an Economic and Social Development and Social Development, among other categories: Quality, Competitiveness, Productivity, Workforce Qualification, Eradication / Combating Poverty / Inequalities / Poverty, an Inclusion / Insertion / Social Rise, Social Justice / Dignity / Citizenship, Research / Science / Technology / Innovation.